Depression Mediates the Relationship between Childhood Trauma and Internet Addiction in Female but Not Male Chinese Adolescents and Young Adults - Xue Dong (MDPI AG, 2021)
Internet addiction is associated with a range of psychological risk factors such as childhood trauma and depression. Studies have also suggested sex differences in internet and other behavioral addictions. However, it remains unclear how childhood trauma, depression and internet addiction inter-relate differently between the sexes. A total of 1749 adolescents and young adults aged 12–27 participated in a survey of sociodemographic characteristics and standardized assessments to evaluate internet addiction (Internet Addiction Test), childhood trauma (Childhood Trauma Questionnaire) and depression (Beck Depression Inventory). Mediation and path analyses were used to examine the relationship between childhood trauma, depression and internet addiction. Internet-addicted females relative to males showed more severe depression but the control participants showed the opposite. Childhood trauma was associated with depression for both internet-addicted males and females; however, internet-addicted females but not males showed significant associations between depression and the severity of internet addiction as well as between childhood trauma and the severity of internet addiction. Further, in females, depression mediated the correlations between all types of childhood trauma and the severity of internet addiction. A path analysis suggested that sexual abuse and emotional neglect contributed most significantly to internet addiction when all types of childhood trauma were examined in one model. The findings suggest sex differences in the relationship between childhood trauma, depression and internet addiction. Childhood trauma contributes to internet addiction through depression only in females. The findings may guide future prevention and intervention strategies of internet addiction.